Comparison of Birth Defects in Infants Conceived by Assisted Reproductive Technologies vs. Naturally Conceived Infants in Mashhad, Iran: - Shahverdi, Ehsan; Vahid Roodsari, Fatemeh; Akhavan Saffar, Masoomeh (Galen Medical Journal, 2015)
Background: Assisted reproductive technologies (ART) are known as a treatment for infertility in which oocyte undergoes manipulation outside body. The aim of this study was to study the evaluation of birth defects in infants conceived through assisted reproductive technologies (ART) and compare them with naturally-conceived infants. Materials and Methods: In this retrospective study, four hundred naturally-conceived infants and 400 infants conceived by ARTs between 20 March and 20 November 2012 in Gha’em Hospital and Sheikh Hospital of Mashhad in Iran participated in this study. Infants were evaluated by a pediatrician at the time of birth, 10 days and 40 days after birth. Correlation between the use of IVF and/or ICSI methods and birth defects was evaluated. Results: Of total 800 infants (450 boys and 350 girls), half of the infants were conceived through natural pregnancy, 200(25%) through in-vitro fertilization (IVF) and 200 (25%) intra- cytoplasmic sperm injection (ICSI). In Infants conceived by IVF, 5 cases (2.5%) had a kind of birth defect just similar to those conceived by ICSI; while 4 cases had birth defects in natural pregnancy. There was no significant correlation between the use of IVF and/or ICSI methods in terms of birth defects (P=0.280).Conclusion: We found that using IVF or ICSI methods is not associated with increasing birth defects.[GMJ.2015;4(4):146-50]